Hubungan Aktivitas Fisik Dengan Kualitas Hidup Pasien Chronic Kidney Disease (CKD) Di Unit Hemodialisa Rumah Sakit Tk. III Dr. Reksodiwiryo Padang - Ike Indriani; Hidayatul Rahmi; Revi Neini Ikbal (Jurnal Sains Farmasi Dan Kesehatan, 2026)
Chronic Kidney Disease (CKD), or kidney failure, is a progressive and irreversible renal dysfunction in which kidney function in maintaining metabolism and fluid and electrolyte balance declines, resulting in uremia. In 2025, there were 368 patients with chronic kidney disease (CKD) in West Sumatra, and 52% of them underwent hemodialysis. The purpose of this study was to determine the relationship between physical activity and quality of life in Chronic Kidney Disease (CKD) patients in the Hemodialysis Unit of Dr. Reksodiwiryo Hospital, Padang, 2025. This study was a quantitative study using a cross-sectional approach. Data collection was conducted from August 4-22, 2025, at the Hemodialysis Unit of Dr. Reksodiwiryo Hospital, Padang. The population of this study was 106 Chronic Kidney Disease (CKD) patients admitted to the Hemodialysis Unit of Dr. Reksodiwiryo Hospital, Padang, from January to March 2025. The sample size was 51 respondents using purposive sampling. Data were analyzed using univariate and bivariate methods using Chi-Square statistical tests. The results showed that more than half (66.7%) had a poor quality of life, and more than half (54.9%) reported light physical activity. There was a relationship between physical activity and quality of life in Chronic Kidney Disease (CKD) patients at the Hemodialysis Unit of Dr. Reksodiwiryo Hospital, Padang (p=0.028). The results of this study concluded that there is a relationship between physical activity and quality of life in Chronic Kidney Disease (CKD) patients. Hospital heads and ward heads are expected to provide information through health education on the relationship between physical activity and quality of life in patients with Chronic Kidney Disease (CKD), so that patients can adapt to their current situation.